Real Wage, Labor Productivity, and Employment Trends in South Africa : A Closer Look - Klein, Nir (IMF Working Papers; Working Paper, 2012)
The paper looks at the dynamics of employment in South Africa and examines the factors that contributed to the job-shedding observed during the recent financial crisis. The paper finds that the rapid growth of the real wage, which outpaced the labor productivity growth in most sectors, played an important role in suppressing employment creation. The paper also finds that while there is a co-integrating link between the real wage and labor productivity, the deviations from equilibrium are persistent and thus contribute to a weak link between real wage growth and labor productivity growth in the short term. This finding is also supported by a cross-country analysis, which shows that in South Africa the link between the real wage and labor productivity is substantially weaker than in other emerging markets, even after controlling for labor market tightness indicators.